Effects of a virtual reality-based exercise program on functional recovery in stroke patients: part 1 - Lee, Kyoung-Hee (Journal of Physical Therapy Science, 2015)
[Purpose]This study aimed to determine the effects of a virtual reality exercise program using the Interactive Rehabilitation and Exercise System (IREX) on the recovery of motor and cognitive function and the performance of activities of daily living in stroke patients. [Subjects] The study enrolled 10 patients diagnosed with stroke who received occupational therapy at the Department of Rehabilitation Medicine of Hospital A between January and March 2014. [Methods] The patients took part in the virtual reality exercise program for 30 minutes each day, three times per week, for 4 weeks. Then, the patients were re-evaluated to determine changes in upper extremity function, cognitive function, and performance of activities of daily living 4 weeks after the baseline assessment. [Results] In the experimental group, there were significant differences in the Korea-Mini Mental Status Evaluation, Korean version of the modified Barthel index, and Fugl-Meyer assessment scores between the baseline and endpoint. [Conclusion] The virtual reality exercise program was effective for restoring function in stroke patients. Further studies should develop systematic protocols for rehabilitation training with a virtual reality exercise program.